DO FEMALE DIRECTORS ENHANCE CSR DISCLOSURE? EMPIRICAL FINDINGS FROM INDONESIA’S SHARIA BANKING SECTOR - Paramita; Suarni, Agusdiwana; Khaliq, Abdul (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This study investigates whether female directors enhance corporate social responsibility (CSR) disclosure in Indonesia’s Sharia banking industry. Using panel data from four Islamic commercial banks from 2019 to 2023, CSR disclosure is measured with the Islamic Social Reporting (ISR) Index, while female board representation is defined as the proportion of women on the board of directors. Firm size, profitability, and leverage are included as control variables. Panel regression techniques were employed after Chow and Hausman tests to determine the appropriate model. The results show that female directors do not have a significant influence on CSR disclosure, indicating that gender diversity has not yet improved reporting practices in Indonesian Islamic banks. In contrast, firm size displays a positive and significant relationship with CSR disclosure, suggesting that larger banks have greater resources and institutional capacity to implement and communicate CSR initiatives. These findings emphasize the importance of structural and institutional factors in shaping CSR transparency and suggest that the effect of gender diversity may be constrained by limited female representation and existing governance norms. The study contributes empirical evidence from a sector governed by unique ethical and regulatory principles and provides insights for policymakers seeking to strengthen sustainable governance.